The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2196/19439
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile App for Self-management of Urgency and Mixed Urinary Incontinence in Women: Randomized Controlled Trial

Abstract: Background Many women experience urgency (UUI) and mixed (MUI) urinary incontinence but commonly hesitate to seek care. Treatment access and self-management for these conditions can be supported through eHealth approaches. Objective This study aimed to investigate the efficacy of the mobile app Tät II for self-management of UUI and MUI in women. Methods This randomized controlled trial included women ≥18 yea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
96
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(96 citation statements)
references
References 42 publications
0
96
0
Order By: Relevance
“…For all three RCTs, there was no face-to-face contact between the study participants, researchers, and healthcare providers throughout the recruitment and treatment processes. Treatment effectiveness was evaluated in the short term (three months) [ 17 19 ] and over the long term (up to two years) [ 20 , 21 ]. Previous studies found that UI treatments that focused mainly on PFMT, provided via the internet or a mobile app, showed clinically relevant improvements in symptoms and in QoL [ 17 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For all three RCTs, there was no face-to-face contact between the study participants, researchers, and healthcare providers throughout the recruitment and treatment processes. Treatment effectiveness was evaluated in the short term (three months) [ 17 19 ] and over the long term (up to two years) [ 20 , 21 ]. Previous studies found that UI treatments that focused mainly on PFMT, provided via the internet or a mobile app, showed clinically relevant improvements in symptoms and in QoL [ 17 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The enrolment process and the inclusion and exclusion criteria for the three RCTs are shown In Table 1 . More detailed data were published previously [ 17 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Community-dwelling women were recruited from all over Sweden, via the project's website (www.tät.nu), and throughout the process there was no face-to-face contact between the study participants, researchers, and healthcare providers in any of the three RCTs. The treatments have been evaluated with regard to effectiveness in the short (three months) [17][18][19] and long (up to two years) term. [20,21] UI treatment focusing on mainly PFMT, provided via internet or a mobile app, showed clinically relevant symptom improvement as well as improvement in QoL.…”
Section: Materials and Methods Econtinencesementioning
confidence: 99%
“…[20,21] UI treatment focusing on mainly PFMT, provided via internet or a mobile app, showed clinically relevant symptom improvement as well as improvement in QoL. [17][18][19][20][21] In Table 1, enrolment process information and inclusion and exclusion criteria for the three RCTs can be found. Further information is also available in the original articles.…”
Section: Materials and Methods Econtinencesementioning
confidence: 99%
See 1 more Smart Citation